Institutional shareholding, common ownership and productivity A cross-country analysis - Bas, Maria (OECD Publishing, 2023)
The increase in institutional ownership, the shift towards passive portfolio management and the rise of common ownership have transformed OECD countries financial markets in the last decades. The paper investigates the potential consequences of these transformations on firm's productivity, using granular data on firms financial and ownership structure as well as a variety of econometric methods. The analysis suggests that the rise of institutional investors is overall not a major concern from a productivity standpoint: firms displaying higher institutional ownership tend to have higher productivity levels and growth rates compared to their peers, though the positive relationship tends to vanish when institutional investors' time horizon is short. Moreover, inter-industry common ownership is related to higher firm-level productivity and this positive relation is stronger for firms operating in intangible-intensive and digital sectors, potentially hinting to an easing of vertical relationships and/or technological spillovers when firms operating in different sectors are owned by the same equity holders. On the contrary, the correlation with intra-industry common ownership appears negative, though not always significantly, potentially due to lower competition
Keywords: Economics